From agrifood cooperatives to learning netchains: toward an interorganizational and interpersonal framework - García Pérez, Ana María; Roman Cervantes, Cándido; García Martínez, Marian (REVESCO. Revista de Estudios Cooperativos, 2015)
This paper presents a theoretical framework grounded on network theory and social capital theory to examine the role of interorganizational and interpersonal networks in agrifood cooperatives in their transition to learning netchains. Our model contents that the higher the degree of horizontal and vertical collaboration along the supply chain the closer the focal firm to the end-consumer and, therefore, to market information. Collaboration requires joint planning and problem resolution, which is in turn positively related to information and knowledge dissemination along the netchain. It further needs new ideas through informal interpersonal networks. This transformation would result in greater satisfaction among cooperative members and customers and higher R&D intensity.